2020
DOI: 10.1002/prep.202000165
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition Pathways of Ammonium Dinitramide (ADN) and its HNO3‐Clusters Elucidated by DFT‐Calculations

Abstract: Ammonium dinitramide (ADN) may serve as a ‘green’ oxidizer for rocket propellants since it provides chlorine free and minimum signature exhaust gases. However, stability issues and an erratic decomposition behaviour limit its non‐questionable general usability. Nitric acid (HNO3) is a decomposition product of ADN and is known to accelerate the decomposition autocatalytically. In this study, we investigate the effect of HNO3 on the initial decomposition steps of ADN via quantum chemical calculations based on de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This leads to the assumption, that ADN decomposes near the surface and forms condensed species, e. g. nitric acid and its clusters and ammonium nitrate, like Lang and Bohn reported for the decomposition of pure ammonium dinitramide [27]. However, the detailed decomposition pathway for an ADN propellant is not fully investigated yet.…”
Section: Resultsmentioning
confidence: 99%
“…This leads to the assumption, that ADN decomposes near the surface and forms condensed species, e. g. nitric acid and its clusters and ammonium nitrate, like Lang and Bohn reported for the decomposition of pure ammonium dinitramide [27]. However, the detailed decomposition pathway for an ADN propellant is not fully investigated yet.…”
Section: Resultsmentioning
confidence: 99%
“…Green and co-workers investigated and established the mechanism for the reactions in the gas phase using transition state theory-based theoretical kinetics. Lang and Bohn found that the formation of the reactive H 2 NO 3 + can accelerate the decomposition of ammonium dinitramide (NH 4 N­(NO 2 ) 2 ) based on the DFT calculations. These reactions may play an important role in HN decomposition, but this is the subject of future study.…”
Section: Results and Discussionmentioning
confidence: 99%